Changes in Protein Synthesis and Morphology during Acid Adaptation of Propionibacterium freudenreichii - Jan, Gwénaël (American Society for Microbiology, 2001)
Survival of bacteria in changing environments depends on their ability to adapt to abiotic stresses. Microorganisms used in food technology face acid stress during fermentation processes. Similarly, probiotic bacteria have to survive acid stress imposed within the stomach in order to reach the intestine and play a beneficial role. Propionibacteria are used both as cheese starters and as probiotics in human alimentation. Adaptation to low pH thus constitutes a limit to their efficacy. Acid stress adaptation in the probiotic SI41 strain of Propionibacterium freudenreichii was therefore investigated. The acid tolerance response (ATR) was evidenced in a chemically defined medium. Transient exposure to pH 5 afforded protection toward acid challenge at pH 2. Protein neosynthesis was shown to be required for optimal ATR, since chloramphenicol reduced the acquired acid tolerance. Important changes in genetic expression were observed with two-dimensional electrophoresis during adaptation. Among the up-regulated polypeptides, a biotin carboxyl carrier protein and enzymes involved in DNA synthesis and repair were identified during the early stress response, while the universal chaperonins GroEL and GroES corresponded to a later response. The beneficial effect of ATR was evident at both the physiological and morphological levels. This study constitutes a first step toward understanding the very efficient ATR described in P. freudenreichii.